Pementasan Busana Tradisional dan Tari Denok Sebagai Strategi Diplomasi Budaya Indonesia di Cabanatuan, Filipina - Muhammad Budi Haryono; Bambang Hadi Kurnayo; Lintang Enggartiasto; Anita Viana; Danu Setiyawan; Ghazy Tara Tsaqif; Anas Asih Werdiyarti; Jason Edmond Wijayanto; Aan Burhanudin; Muchammad Malik; Rifki Hermana; Agus Mukhtar; Rizky Muliani Dwi Ujianti (CV. IRA PUBLISHING, 2026)
Culture is the primary identity of a nation, to be preserved and passed down through generations. Cultural preservation of local Indonesian heritage, such as traditional costumes and dances, faces significant challenges in the era of globalization. With its cultural richness, Indonesia utilizes cultural diplomacy as a form of soft power to introduce and preserve its cultural heritage on the international stage, including in Cabanatuan City, Philippines. This community service activity aims to socialize various traditional Indonesian costumes and the Tari Denok dance to the residents of Cabanatuan City. The event was held at Nueva Ecija University of Science and Technology in the Philippines. The method used was socialization through performances of traditional attire and Tari Denok, attended by more than 500 participants. The performances of traditional costumes and Tari Denok were divided into two days: August 22, 2025, and September 11, 2025. The results of this activity demonstrate strong enthusiasm among residents of Cabanatuan City for Indonesian culture. The results of this activity increased participants' knowledge and understanding of various traditional Indonesian clothing and Tari Denok.